Perancangan Buku Photography Story Tari Remo Sebagai Upaya Melestarikan Kesenian Tari Tradisional Surabaya - Anggara, Bayu; Budiardjo, Hardman; Yuan, Dhika (Jurnal Art Nouveau, 2017)
Remo dance is an opening dance of an event and dance typical of East Java that has meaning about the courage of a prince. Remo dance can be obtained from within a person's soul and the emotions that represent the people of East Java. Remo dance started in District Diwek, Ceweng, Jombang regency in 1850. originally this dance was created by some singers dance at that time. In the era of Cak Durasim in 1927 Remo dance was successfully performed in Surabaya society which was presented in the opening of Ludruk theater and other cultural performances. The lack of public understanding of the meaning of the Remo Dance movement attracts researchers to preserve local culture with the cultural conditions of Indonesia that are beginning to disappear by outside cultural values, aimed at not being eroded by the times. The development of the current era is more advanced, especially people living in big cities know less and understand about traditional dance dance Remo. This is due to the lack of insight into the traditional dance arts that are consumed by modern times today, due to the less desirable cultural preservation. The displacement of traditional art by the development of the times can be understood because the exposure to the community is less informative. The purpose of the researcher is to design the story photography of remo dance book as an effort to preserve the traditional dance arts of Surabaya with a focus on the meaning of a movement and the meaning contained within the movement. From the results of the analysis of the data then the concept obtained is Expressive which has a meaning as a picture or expression of traditional art Remo dance. and then, the story photography of remo dance book designed by investigators as evidence Surabaya preserve traditional dance arts that have an authentic cultural values strong Keywords : Story Photography, Remo Dance, Expressive, Surabaya Traditional Dance